Free Pass Through the Pillars of Hercules? Genetic and Historical Insights Into the Recent Expansion of the Atlantic Blue Crab Callinectes sapidus to the West and the East of the Strait of Gibraltar - González-Ortegón, Enrique; Berger, Selina; Encarnação, João; Chairi, Hicham; Morais, Pedro; Teodósio, Maria Alexandra; Oliva-Paterna, Francisco J.; Schubart, Christoph D.; Cuesta, Jose A. (Frontiers in Marine Science, 2022)
The invasive Atlantic blue crab Callinectes sapidus has considerably extended its distribution along the Gulf of Cadiz and Moroccan coasts in the northeast Atlantic. This could indicate a new introduction event in the Gulf of Cadiz from the native area, in case of detectable genetic differences from the Mediterranean Sea populations. To test this and reconstruct the invasion, we assessed the genetic structure of crabs in the Gulf of Cadiz and Alboran Sea. We used sequences of the mitochondrial gene cytochrome c oxidase subunit I (COI), in almost its full length (1511 basepairs), of 149 individuals from three sites along the Spanish Mediterranean coast, two in the Alboran Sea, and two in the Gulf of Cadiz. Our data reveal low genetic variability, with only two haplotypes (here referred to as CSWM1 and CSWM2), compared to its known high genetic diversity in the native range, indicating a strong founder effect in the study region. Here we document an inversion of haplotype predominance between regions, haplotype CSWM2 being dominant in most of the Spanish Mediterranean coast, but less frequent in the Gulf of Cadiz and Alboran Sea. This suggests a secondary introduction of propagules into the investigated area, rather than a new introduction from the native area, nor a natural westward expansion with environmental selection of one haplotype over the other. Further studies with additional populations would help to better unveil the history of yet another invasive species in the Gulf of Cadiz.